Hubungan Koordinasi Mata Tangan Dan Kecepatan Dengan Kemampuan Dribbling Bola Basket Atlet Putra Tembilahan Basket Ball Club (Tbbc) Junior Tembilahan Kabupaten Idragiri Hilir - Alatas, Sy. Mirlinarafiqatihafizhaty; Pratama, Niko Zulni (Jurnal Edukasi, 2024)
The problem in this study is the number of athletes who failed to do Dribbling like the ball out of the field, the ball freed from control so that the ball fell in the opponent's hands, still weak coordination of the hand and speed with the ability to Dribble basketball athlete son Tembilahan basketball ball club (tbbc) junior Tebilahan district Indragiri Hilir. The method used in this research is that the method of quantitative research can be understood as a method of research based on the philosophy of positivism, used to research on a particular population or sample, sampling techniques are generally performed randomly, compilation of data using research instruments, data analysis is quantitaf/statistic with the purpose to test the hypothesis that has been established. This research is a type of correlational research, correlation research is research to find out whether there is a relationship between two variables or several variables. The sampling technique in this study is a total sample of 14 people. From the results of the research obtained correlation coefficient (rx1y) rtable 0.532 It turns out rhitung 0.6623 > rtable 0,532 so that Ho is rejected and Ha is accepted and the distribution test t showed It Turns out thitung 4.822 > ttable 2.718 so Ho is received and Ho is refused. From the result of the calculation of the product moment correlations ( rx2y) Rtable 0.532 It Turned out rhiting 0.8412 > rtabel 0.532 so Ho has been rejected and Ha has been accepted, and distribution testing t shows It turned out Thitung5.3847 > tables2.718 So that Ho and Ho are accepted.